The pleasant surprise of Easter eggs in the cinema: analysis with eye-tracking and facial recognition - Martínez Martínez, Luz (2025)
Easter eggs are hidden elements that enrich the cinematic experience by generating surprise, curiosity, and emotional connection. This study aims to analyze the attentional and emotional impact of Easter eggs in animated films through neurocognitive tools, highlighting their potential as narrative and marketing resources. Methodology. An intra-subject experimental design was conducted with a sample of 22 participants aged between 18 and 50. Six frames from Disney and Pixar films featuring Easter eggs of varying complexity and narrative integration were analyzed. Eye-tracking, facial recognition, and questionnaires were used to measure visual attention, emotions, and engagement. Results and conclusions. The results show that Easter eggs significantly capture attention, increase engagement, and elicit positive emotions such as surprise and joy. Their active integration into the action enhances their impact. The complexity of the Easter egg influences its recognition and emotional intensity, although excessive complexity may hinder detection. These findings reinforce their value as tools to enhance the audiovisual experience and strengthen audience loyalty. Original contribution. This study provides empirical evidence—using neurocognitive technologies—of the positive effect of Easter eggs on viewers’ attention and emotions. It stands out as an innovative contribution to the development of immersive narratives in audiovisual content and to brand communication strategies based on emotional involvement and surprise.